Vita umana e morte umana: una nuova definizione - Gatti, Maria Gabriella (Il sogno della farfalla, 2009)
The Harvard protocol of 1968 with its definition of cerebral death has opened the way to a new anthropology that has raised questions that have given rise to the birth of a new discipline “bioethics”. The latter, both from its metaphisic-religious declension as well as its illuministic-rationalistic reading, has questioned the capacity of medicine to respond in technical-scientific terms, to the interrogatives on “human nature”. The abstract proposes an interpretation of the experimental and biological data relative to the ontogenisis of sensibility to pain. It is possible to make an analogy between brain functioning in a vegetative state and in the foetus. In both cases there is a disconnection among cerebral areas. Whilst in the foetus disconnection is functional and is linked to an inhibitory effect of the various hormones secreted in cerebral substance and the placenta, in the permanent vegetative state it is pathological in that it is brought about by the destruction of vast cortical and subcortical areas. Consequently it is legitimate to think both for the vegetative and foetal states, as modern medicine tends to do, that only automisms and neurological reflexes are possible in relation to nociceptor stimuli, but not to mental activity, neither of the conscious nor of the non-conscious or irrational type which characterizes human birth.